Addressing social isolation in high-rise residential buildings in Kuala Lumpur - Lee, Nur Irdina; Mohd Noor, Mohd Zairul; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2024)
As the urban population grows, the construction of high-rise buildings has increased, often prioritizing functionality and aesthetics over community interactions. This study explores how architectural design can mitigate social isolation by fostering social connections among residents. The research identifies the lack of communal spaces and the cultural preference for privacy as significant factors contributing to social isolation. It also examines how integrating green and communal spaces can enhance social interactions. The study employs a mixed-method approach, including spatial analysis and surveys, to identify architectural strategies that promote social cohesion. The findings highlight the importance of designing high-rise buildings that not only optimize space but also create environments that encourage meaningful social interactions, ultimately improving residents' well-being and the overall health of the urban community.